THERMODYNAMIC ANALYSIS OF ROTARY CONTROL HEAD LUBRICATION AND COOLING SYSTEM - HU Gang; WANG GuoRong; YUAN GuangJie; XIA Yan; LI QuanChang; CHEN BaoKang (Jixie qiangdu)
According to the requirements of the CBM special rotary control head lubrication and cooling system and combined with the existing mature rotary control head lubrication cooling technology,this paper designed a structure without cooling and lubricating pump station plugins. In order to ensure the structure satisfies the lubrication and cooling requirements of the rotary control head sealing system and bearing group,this paper applied the finite element analysis software and indoor experiment to carry out the thermodynamic analysis on the rotary control head lubrication and cooling system. The results show that the lubrication and cooling system meets the design requirements. The upper stabilizing bearing temperature is highest which is 71. 9 ℃ while the highest temperature of the dynamic seal assembly is 60℃. In addition,eccentricity,sealing pressure and rotating speed have greater impact on the lubrication and cooling system,the system temperature changes with the above three factors similarly to a linear change.